HUBUNGAN PENGETAHUAN DENGAN KEPATUHAN DIET PADA PENDERITA DIABETES MELLITUS DI POSYANDU LANSIA CEMPAKA KELURAHAN TEMBOK DUKUH KECAMATAN BUBUTAN SURABAYA - Nobel Bistara, Difran; Ainiyah, Nur (Universitas Nahdlatul Ulama Surabaya, 2018)
Diabetes mellitus (DM) is a degenerative disease that can be controlled with the four pillars of management. One of the pillars is compliance in the implementation of the diet